Determination of fentanyl and norfentanyl in cerumen in the setting of postmortem investigation. Issue 5 (1st June 2022) - Mastrogianni, Orthodoxia; Kevrekidis, Dimitrios Phaedon; Brousa, Evdokia; Orfanidis, Amvrosios; Zagelidou, Heleni; Raikos, Nikolaos
Abstract: Cerumen is an emerging alternative biological matrix in the field of forensic toxicology. An ultra‐high‐pressure liquid chromatography–mass spectrometry/mass spectrometry [UHPLC–MS/MS] method for the determination of fentanyl and norfentanyl in cerumen was developed and applied in a mixed drug toxicity fatal case. The method was found to be selective and sensitive (LOQ: 0.05 ng/mg for fentanyl and 0.02 ng/mg for norfentanyl), while validation included recovery, carryover, short‐term stability, matrix effect, accuracy, and precision (RSD%). Accuracy ranged from 83.1% to 103.5%, while intra‐ and inter‐day precision ranged from 8.6% to 13.1% and from 8.3% to 15.8%, respectively. Matrix effect experiments showed that matrix did not significantly affect signal intensity (82.3%–96.8%). Short‐term stability concerning sample extracts was found satisfactory. Fentanyl and norfentanyl were detected in cerumen at a concentration of 1.17 and 0.36 ng/mg respectively. The findings in cerumen corroborate the cause of death and suggest that cerumen is a potential specimen for detecting drugs of abuse in forensic cases.